Energy environmental impact of functional units of a university building - Forte, J. P. P.; Rato, V. (13th REHVA World Congress, CLIMA 2019, 2019)
This paper presents the results of a qualitative assessment of the environmental impact of a set of functional units of a university building, considering negative impacts such as the ones originated by energy, water and resource usage, as well as waste production, but also positive impacts like the ones that may be derived from teaching and learning and from research. This paper is focused on the energy -related environmental impacts which are the most significant. The assessment is performed for three evaluation scenarios: Two of these scenarios are based on the actual condition of the building facilities and its use patterns and differ from each other in the level of severity attributed to each impact criteria. The third scenario has as additional input the future condition of electric energy production through the installation of photovoltaic (PV) panels (which is in progress). According to the assessment carried out, the implementation of the PV panels may have an important contribution in reducing the environmental impact related to the use of the building.